Translabial intrapartum ultrasound in determining duration of the second stage of labor - Zúñiga, Renato (2014)
Evaluation of the second stage of labor is still subjective. Translabial intrapartum ultrasound is an objective evaluation tool of progression of the various stages of childbirth. Objectives: To determine the usefulness of translabial intrapartum ultrasound study in determining duration of the second stage of labor. Design: Observational, prospective and relationship study. Setting: Honorio Delgado Regional Hospital, Arequipa, Peru. Participants: Women in the second stage of labor. Interventions: From April through July 2012 53 patients in second stage of labor and who delivered vaginally underwent translabial ultrasound assessment of variety of position, direction, and angle of progression of the cephalic descent and its relation with duration of the second stage. Main outcome measures: Relation of cephalic descent and duration of the second stage. Results: There was a significant statistical relation (P < 0.05) between progression of the cephalic descent angle and duration of the second stage. According to simple linear regression, a greater progression angle predicted less duration of the second stage of labor. There was also statisticallysignificant relationship (P < 0.05) between duration and direction of the cephalic descent. Finally, the relationship between time and the variety of presentation was statistically significant (P < 0.05). Conclusions: Determination of the range of position, angle of progression and direction of the cephalic descent by using translabial ultrasound was useful to determine the duration of the second stage.Keywords: Translabial ultrasound, progression angle, direction of the cephalic descent, variety of position.